2001
DOI: 10.1055/s-2001-15795
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Dysfunction, Pulmonary Hypertension, Obesity, and Sleep Apnea

Abstract: The purpose of this study was to determine the frequency of central and obstructive sleep apnea in adult patients who have echocardiographic evidence of left ventricular dysfunction and pulmonary hypertension. Subjects with left ventricular dysfunction, pulmonary hypertension (pulmonary artery systolic pressure >30 mm Hg) and no lung disease were evaluated for risk factors associated with pulmonary hypertension. Of eight eligible adults, six completed the study. Subjects were from suburban and inner city famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Several retrospective studies have also found a strong association between OSA and pulmonary hypertension, possibly because of hypoxemia, hypercapnia, and increased sympathetic activity. 119 In a study of 20 ambulatory patients visiting a suburban family practice clinic presenting with unexplained bilateral leg edema and echocardiographic evidence of pulmonary hypertension, almost all the subjects were obese and 60% of them had OSA without evidence of daytime hypoxemia. 120 Currently, there is a paucity of data to support a causal relationship between pulmonary hypertension and obesity.…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
“…Several retrospective studies have also found a strong association between OSA and pulmonary hypertension, possibly because of hypoxemia, hypercapnia, and increased sympathetic activity. 119 In a study of 20 ambulatory patients visiting a suburban family practice clinic presenting with unexplained bilateral leg edema and echocardiographic evidence of pulmonary hypertension, almost all the subjects were obese and 60% of them had OSA without evidence of daytime hypoxemia. 120 Currently, there is a paucity of data to support a causal relationship between pulmonary hypertension and obesity.…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%